2004
DOI: 10.1542/peds.114.1.e16
|View full text |Cite
|
Sign up to set email alerts
|

Underimmunization Among Children: Effects of Vaccine Safety Concerns on Immunization Status

Abstract: ABSTRACT. Objective. To examine the attitudes, beliefs, and behaviors of parents whose children were underimmunized with respect to >2 vaccines that have recently received negative attention, compared with parents whose children were fully immunized with respect to the recommended vaccines.Design. Case-control study. Setting. A sample of households that participated in the National Immunization Survey were recontacted in 2001.Main Outcome Measure. Vaccination status was assessed. Case subjects were underimmuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
1
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(180 citation statements)
references
References 21 publications
(25 reference statements)
6
162
1
11
Order By: Relevance
“…15 Parents attitude has a significant impact on vaccination status of children. 16 Almost all of the parents believe that compliance to the immunization schedule is important (96%), and this percentage is higher compared to a study done by Bernsen et al in the United Arab Emirates. 17 In this study, 96% of parents found to believe that all the children in the community should receive vaccination which was higher compared to a study conducted at Libya.…”
mentioning
confidence: 85%
“…15 Parents attitude has a significant impact on vaccination status of children. 16 Almost all of the parents believe that compliance to the immunization schedule is important (96%), and this percentage is higher compared to a study done by Bernsen et al in the United Arab Emirates. 17 In this study, 96% of parents found to believe that all the children in the community should receive vaccination which was higher compared to a study conducted at Libya.…”
mentioning
confidence: 85%
“…Children who are underimmunized are more likely to have parents who have attitudes, beliefs, and behaviors indicative of concerns of safety of vaccines [2,15]. At the same time, concerns about the safety of vaccination are also prominent in parents who immunize [16]. In one national telephone survey of parents, most parents understood the benefits of vaccination, but many had significant misconceptions that acted to decrease their confidence in vaccines [17].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine safety is an important factor in mothers' choices regarding vaccine utilization in other countries. 12 Research results might also be influenced by historical memories regarding fears about vaccination in Japan. 4,13 In 2011, fatalities after successive injection of Hib vaccine and/or PCV7 and/or other vaccines were reported.…”
Section: Discussionmentioning
confidence: 99%